2000
DOI: 10.1034/j.1600-0501.2000.110207.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year prospective clinical and radiographic study of non‐submerged dental implants

Abstract: Osseointegrated implants as anchors for various prosthetic reconstructions have become a predictable treatment alternative. It was expected that implants required submucosal placement during the healing period for successful tissue integration. However, it has been demonstrated that healing and long-term health of implants could be achieved with equal predictability in a 1-stage, non-submerged approach. This prospective 5-year study not only calculates implant success by life table analysis, but also evaluates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
87
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(109 citation statements)
references
References 14 publications
20
87
0
2
Order By: Relevance
“…Published data described a mean marginal bone loss of 0.4-0.5 mm during the first year post-implantation and 0.05-0.1 mm annually thereafter [7,14]. Similar observations were noted later by other research groups [16,21,22], who defined the following measurements for the one stage ITI implants: 0.75 mm after the first year and less than 0.1 mm the following years. Another study determined that a mean crestal bone loss ranging from 0.9-1.6 mm in the first year after functional loading was acceptable [17].…”
Section: Annual Peri-implant Bone Losssupporting
confidence: 69%
See 3 more Smart Citations
“…Published data described a mean marginal bone loss of 0.4-0.5 mm during the first year post-implantation and 0.05-0.1 mm annually thereafter [7,14]. Similar observations were noted later by other research groups [16,21,22], who defined the following measurements for the one stage ITI implants: 0.75 mm after the first year and less than 0.1 mm the following years. Another study determined that a mean crestal bone loss ranging from 0.9-1.6 mm in the first year after functional loading was acceptable [17].…”
Section: Annual Peri-implant Bone Losssupporting
confidence: 69%
“…This measurement was carried out on both mesial and distal implant sides [15][16][17], on the 5-year postoperative radiographs. When unclear, the most apical bone-to-implant contact, corresponding to the worst case scenario was taken into account.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have looked for correlations between bone loss and clinical parameters among them probing. They concluded that probing depths are of limited value in predicting future peri‐implant bone loss (Dierens et al., 2012; Giannopoulou, Bernard, Buser, Carrel & Belser, 2003; Weber, Crohin & Fiorellini, 2000). Long‐term clinical studies have clearly shown that the probing depth of healthy peri‐implant mucosa is not always smaller than 4 mm but very often up to 6 mm (Dierens et al., 2012; Karoussis et al., 2004; Lekholm et al., 1986).…”
Section: Introductionmentioning
confidence: 99%